2014
DOI: 10.5152/tjar.2014.83436
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis and Acute Kidney Injury

Abstract: Acute kindney injury (AKI) is a clinical syndrome which is generally defined as an abrupt decline in glomerular filtration rate, causing accumulation of nitrogenous products and rapid development of fluid, electrolyte and acid base disorders. In intensive care unit sepsis and septic shock are leading causes of AKI. Sepsis-induced AKI literally acts as a biologic indicator of clinical deterioration. AKI triggers variety of immune, inflammatory, metabolic and humoral patways; ultimately leading distant organ dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…Multiple inflammatory mediators and enzymes participate in organism damage; however, the kidney is the most sensitive organ in sepsis infection [1]. Acute kidney injury (AKI) is a clinical syndrome caused by a variety of pathogens, leading to morbidity and mortality in patients [2]. The pathogenesis is complicated, including pro-inflammatory cytokines, ROS, and cell apoptosis [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple inflammatory mediators and enzymes participate in organism damage; however, the kidney is the most sensitive organ in sepsis infection [1]. Acute kidney injury (AKI) is a clinical syndrome caused by a variety of pathogens, leading to morbidity and mortality in patients [2]. The pathogenesis is complicated, including pro-inflammatory cytokines, ROS, and cell apoptosis [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The predictors that determine AKI in our study were comparable to previous studies. For instance, patient age [8,24,27], sepsis at ICU admission [9], SOFA non-renal score [1,28], emergency surgery [8,24], and perioperative blood lost [29].…”
Section: Discussionmentioning
confidence: 99%
“…The authors stated that medications that have long been successful in animals for the treatment of ARF have unfortunately not been similarly effective in most people experiencing sepsis and sepsis shock in intensive care units. They further suggested that sepsis is a common cause of death and that this necessitated new investigations into the diagnosis and treatment of sepsis-related ARF [31]. On the other hand, Souza et al [32] stated that exposure to P. aeruginosa may cause septic shock, especially in patients with chronic renal failure.…”
Section: Discussionmentioning
confidence: 99%